Implementasi Manajemen BUMDes Desa Tanjung Luar Untuk Meningkatkan Pendapatan Asli Desa Tanjung Luar - M. Saipul Watoni; Kamaruddin; M. Ali Fikri (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2023)
Village Enterprises (BUMDes) are legal entities and are not Again business entities where BUMDes in a way independently manage asset villages, manage efforts, and can weave partnerships with wide companies and institutions private others with the objective can increasing sumder power man in give birth to creative and innovative ideas for develop potentials village. This research aims to determine the implementation of management in business entities owned by Tanjung Luar Village to increase the village's original income and also to what extent these business entities owned by Tanjung Luar Village play a role in increasing the village's original income. In research this, the researcher used method qualitative with method descriptive as well as analysis. Next, the data is taken with technique data collection via observation, interviews, and documentation that the subject study researcher is the head of Tanjung Luar village, chairman of BUMDes, and related people with BUMDes Tanjung Luar village. From the results of the research obtained, implementation management in Tanjung Luar village does not walk with Good so the impact role of BUMDes in adding income original village is no good. For That needs to be implemented implementation management with OK, OK That planning, implementation, and evaluation.